Identification of Candidate Biomarker ASXL2 and Its Predictive Value in Pancreatic Carcinoma - Wang, Gaoming; Yang, Ludi; Gao, Jinli; Mu, Huiling; Song, Yanxiang; Jiang, Xiaohua; Chen, Bo; Cui, Ran (Frontiers in Oncology, 2021)
Pancreatic adenocarcinoma is one of the most lethal diseases with a 5-year survival rate of about 8%. ASXL2 is an epigenetic regulator associated with various tumors including colorectal cancer, breast cancer, and myeloid leukemia. However, the role of ASXL2 in pancreatic cancer remains unclear. This is the first research focusing on the prognostic value of ASXL2 in pancreatic cancer. In this research, we aimed to explore the correlation between ASXL2 and the prognosis, as well as other features in PAAD. We obtained gene expression profiles of PAAD and normal tissues from TCGA, GEO, and Xena databases. TIMER and CIBERSORT algorithms were employed to investigate the effect of ASXL2 on tumor microenvironment. GSEA along with GO and KEGG enrichment analyses were conducted to uncover the biological functions of ASXL2. The response to various chemotherapeutic drugs was estimated by algorithms in R package “pRRophetic”, while the sensitivity to immunotherapy was quantified by TIDE score. We found that ASXL2 was upregulated in the PAAD samples and elevated expression of ASXL2 was linked to poor overall survival. ASXL2 DNA methylation contributed to ASXL2 expression. Functional annotation indicated that ASXL2 was mainly involved in inflammatory response and epithelial mesenchymal transition. Patients with high ASXL2 expression were more likely to benefit from immune checkpoint blockade, gemcitabine, and mitomycin-C. Finally, external datasets and biospecimens were used and the results further validated the aberrant expression of ASXL2 in PAAD samples. In summary, our results highlight that ASXL2 is a potential prognostic and predictive biomarker in pancreatic cancer.